P81 Novel synthetic clot analogs for in-vitro stroke modelling. (29th August 2022) - Guerreiro, H; Wortmann, N; Andersek, T; Ngo, TN; Frölich, A; Krause, D; Fiehler, J; Kyselyova, A; Flottmann, F
Abstract : Introduction: The increased demand for training of mechanical thrombectomy in ischemic stroke urges the creation of new simulation models for training and device assessment. Clot characterization has shown to play a role in procedural planning and thrombectomy device effectiveness. Aim of the Study: In this study, we aim to analyze the characteristics and applicability of completely synthetic, animal-free clots developed by the authors, in the setting of an in-vitro model of mechanical thrombectomy. Methods: Synthetic clots based on agarose (n=12) and silicone (n=11) were evaluated in a previously described in-vitro neurointervention simulation of mechanical thrombectomy with clot extraction devices. 9 clots were excluded due to insufficient vessel occlusion and failure to integrate with clot extraction device. Synthetic thrombi were characterized and compared using a categorical score-system on vessel occlusion, elasticity, fragmentation, adherence and device integration. Results: Both agarose-based and silicone-based clots demonstrated relevant flow arrest and a good integration with the clot extraction device. Silicone-based clots scored higher on adherence to the vessel wall and elasticity. Calcified clots of mixed nature were simulated with addition of 3D printed structures. Conclusion: Selected synthetic clots can successfully be implemented in an in-vitro training environment of mechanical thrombectomy. The clots' different properties might serve to mimic fibrin-rich and red blood cell human thrombi. References: Nadine Wortmann, Thomas Andersek, Helena Guerreiro, et al . Development of Synthetic Thrombus Models to Simulate Stroke Treatment in a Physical Neurointerventional Training Model, All Life 2022;15:1, 283–301, DOI:10.1080/26895293.2022.2046181 Spallek J, Kuhl J, Wortmann N, et al . Design for Mass Adaptation of the Neurointerventional Training Model Hannes with Patient-specific Aneurysm Models. Proceedings of the Design Society: International Conference on Engineering Design . 2019;1 (1):897–906. DOI:10.1017/DSI.2019.94 Do you have any conflict of interest to declare? : No